Hydrotherapy as a recovery strategy after exercise: a pragmatic controlled trial - Cuesta-Vargas, Antonio; Travé-Mesa, Álvaro; Vera-Cabrera, Alberto; Cruz-Terrón, Dario; Castro-Sánchez, Adelaida María; Fernández-de-Las-Peñas, César; Arroyo Morales, Manuel (BMC Springer Nature, 2013)
Background: Our aim was to evaluate the recovery effects of hydrotherapy after aerobic exercise in cardiovascular, performance and perceived fatigue. Methods: A pragmatic controlled repeated measures; single-blind trial was conducted. Thirty-four recreational sportspeople visited a Sport-Centre and were assigned to a Hydrotherapy group (experimental) or rest in a bed (control) after completing a spinning session. Main outcomes measures including blood pressure, heart rate, handgrip strength, vertical jump, self-perceived fatigue, and body temperature were assessed at baseline, immediately post-exercise and post-recovery. The hypothesis of interest was the session*time interaction. Results: The analysis revealed significant session*time interactions for diastolic blood pressure (P=0.031), heart rate (P=0.041), self perceived fatigue (P=0.046), and body temperature (P=0.001); but not for vertical jump (P=0.437), handgrip (P=0.845) or systolic blood pressure (P=0.266). Post-hoc analysis revealed that hydrotherapy resulted in recovered heart rate and diastolic blood pressure similar to baseline values after the spinning session. Further, hydrotherapy resulted in decreased self-perceived fatigue after the spinning session. Conclusions: Our results support that hydrotherapy is an adequate strategy to facilitate cardiovascular recovers and perceived fatigue, but not strength, after spinning exercise.
Keywords: Hidroterapia; Hydrotherapy; Heart rate; Fatigue; Strength; Blood pressure; Body temperature